(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Objective: The objective of this study was to determine the knowledge and perception about quality assurance process in education among university students. Methods: The study was cross-sectional in design with anonymous, structured, and close-ended questionnaire with 16 items administered to university students. The demographic information was collected including gender and level of study. The overall knowledge scores were determined and compared between genders and educational levels. Data was analysed for descriptive statistics using Statistical Package for Social Sciences 20.0 with P < 0.05 as statistically significant. Results: The questionnaire was given to 500 university students and 419 responded with an overall response rate of 83.8%. Of these 419 participants, 65.4% (n=274) were males and 34.6% (n=145) were females. 46.77% (n=196), 36.51% (n=153), 16.72% (n=70) were pursuing undergraduate programs, postgraduate programs and other programs respectively. Only 54.25% (n=227) of university students had adequate knowledge about the quality assurance process. There was no statistically significant difference in the knowledge score between males and females and also between the undergraduate students, postgraduate students and other program students. Conclusion: The findings of our study indicate the limited knowledge and participation of university students in quality assurance process. In order to achieve quality in education, polices should be implemented to encourage the students for their active participation in the quality assurance activities and to provide adequate training to enhance their knowledge.